Selected readings on telecommunications and networking [ - Gutierrez, Jairo , 1960- (Information Science Reference, 2009)
"This book presents quality articles focused on key issues concerning the planning, design, maintenance, and management of telecommunications and networking technologies"--Provided by publisher